2020
DOI: 10.1021/acs.langmuir.0c01964
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Lipid Membranes through Partitioning of the Blood Bag Plasticizer Di-2-ethylhexyl phthalate (DEHP)

Abstract: The safe storage of blood is of fundamental importance to health care systems all over the world. Currently, plastic bags are used for the collection and storage of donated blood and are typically made of poly­(vinyl chloride) (PVC) plasticized with di-2-ethylhexyl phthalate (DEHP). DEHP is known to migrate into packed red blood cells (RBC) and has been found to extend their shelf life. It has been speculated that DEHP incorporates itself into the RBC membrane and alters membrane properties, thereby reducing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 39 publications
7
25
1
Order By: Relevance
“…Even though the presence of DEHP could potentially explain the observed increased stiffness in our experiments, we could not find clear evidence for the presence of DEHP molecules in the electron density of RBC cm s in our X-ray diffraction results. The upper bound of experimentally reported DEHP concentrations in blood bags is � 600 μg/ml [68], which corresponds to molar concentrations of less than 0.2 mol%, significantly smaller than what was used in [70]. While we can not rule out that the effects of DEHP were too small to be detected in this study, we speculate that the changes in the membranes' structural parameters would be even smaller than the subtle effects reported by Bider et al…”
Section: Plos Onecontrasting
confidence: 53%
See 1 more Smart Citation
“…Even though the presence of DEHP could potentially explain the observed increased stiffness in our experiments, we could not find clear evidence for the presence of DEHP molecules in the electron density of RBC cm s in our X-ray diffraction results. The upper bound of experimentally reported DEHP concentrations in blood bags is � 600 μg/ml [68], which corresponds to molar concentrations of less than 0.2 mol%, significantly smaller than what was used in [70]. While we can not rule out that the effects of DEHP were too small to be detected in this study, we speculate that the changes in the membranes' structural parameters would be even smaller than the subtle effects reported by Bider et al…”
Section: Plos Onecontrasting
confidence: 53%
“…The partitioning of DEHP in RBC cm s has long been suspected to change membrane properties [68,69] and contribute to the changes observed during storage. A recent study in model lipid bilayers indeed reported that DEHP can increase membrane width and area per lipid, and the deuterium order parameter, however, decrease membrane orientation, indicating the formation of thicker, stiffer membranes with increased local curvature [70]. Concentrations of DEHP in this paper were elevated, of up to 10 mol% of the lipid concentration, to emphasize the potential effects of DEHP.…”
Section: Plos Onesupporting
confidence: 50%
“…A total of 4 simulation systems were created. All-atom simulations can provide a detailed insight into membrane structure and dynamics but are limited to small systems due to the increased computation time [50][51][52]. Coarse grained models are thus used to study large-scale membrane and protein dynamics.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…As reported by Sici ńska (2019) [18], PAEs have the potential to induce apoptotic in human peripheral blood mononuclear cells, and one of the important characters of apoptosis is the change of membrane permeability. Bider et al found that the presence of DEHP in the bilayers will alter membrane properties, like membrane thickness, width, order parameters, and acyl chain orientation [19]. Similar results were observed in some other small molecule-membrane systems, such as butanol [20], thymol [21], propofol, and fentanyl [22].…”
Section: Introductionmentioning
confidence: 60%